Quantitative Analysis of the Trade Industry: The Effect of Environmental Policy on Industry Growth - Ahmad Nur Budi Utama; Zumrotul Avifa K; Diah Nurdiana; Rusni Andriani; Hasnadia Rusdi (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
This study aims to examine the impact of environmental policies on the growth of the trade industry, with a particular focus on Toko Marannu. Through a descriptive analysis, the research highlights key areas of implementation, customer acceptance, and the resultant effects on sales, customer satisfaction, and overall business performance. The findings reveal that Toko Marannu has successfully implemented environmental policies, such as the use of environmentally friendly bags and the provision of alternative packaging options, which have been well-received by customers. The study shows that these policies positively influence sales growth, increase the number of visitors, and enhance profits, while maintaining high levels of customer satisfaction. The research, conducted through a quantitative approach using surveys and questionnaires with 40 customers, underscores the importance of environmental policies in driving industrial growth and improving consumer perceptions. These insights offer valuable guidance for businesses seeking to integrate sustainable practices while achieving economic growth.